Functions of RNA N6-methyladenosine modification in acute myeloid leukemia - Xue Zheng; Yuping Gong (BMC, 2021)
Abstract Acute myeloid leukemia (AML) is a hematologic malignancy with an unfavorable prognosis. A better understanding of AML pathogenesis and chemotherapy resistance at the molecular level is essential for the development of new therapeutic strategies. Apart from DNA methylation and histone modification, RNA epigenetic modification, another layer of epigenetic modification, also plays a critical role in gene expression regulation. Among the more than 150 kinds of RNA epigenetic modifications, N6-methyladenosine (m6A) is the most prevalent internal mRNA modification in eukaryotes and is involved in various biological processes, such as circadian rhythms, adipogenesis, T cell homeostasis, spermatogenesis, and the heat shock response. As a reversible and dynamic modification, m6A is deposited on specific target RNA molecules by methyltransferases and is removed by demethylases. Moreover, m6A binding proteins recognize m6A modifications, influencing RNA splicing, stability, translation, nuclear export, and localization at the posttranscriptional level. Emerging evidence suggests that dysregulation of m6A modification is involved in tumorigenesis, including that of AML. In this review, we summarize the most recent advances regarding the biological functions and molecular mechanisms of m6A RNA methylation in normal hematopoiesis, leukemia cell proliferation, apoptosis, differentiation, therapeutic resistance, and leukemia stem cell/leukemia initiating cell (LSC/LIC) self-renewal. In addition, we discuss how m6A regulators are closely correlated with the clinical features of AML patients and may serve as new biomarkers and therapeutic targets for AML.